Knockdown of FBI-1 Inhibits the Warburg Effect and Enhances the Sensitivity of Hepatocellular Carcinoma Cells to Molecular Targeted Agents via miR-3692/HIF-1α - Liu, Juan; Yang, Chao; Huang, Xiao-Mei; Lv, Pan-Pan; Yang, Ya-Kun; Zhao, Jin-Na; Zhao, Si-Yuan; Sun, Wan-Jun (Frontiers in Oncology, 2021)
The transcription suppressor factor FBI-1 (the factor that binds to inducer of short transcripts-1) is an important regulator of hepatocellular carcinoma (HCC). In this work, the results showed that FBI-1 promoted the Warburg effect and enhances the resistance of hepatocellular carcinoma cells to molecular targeted agents. Knockdown of FBI-1 via its small-interfering RNA (siRNA) inhibited the ATP level, lactate productions, glucose uptake or lactate dehydrogenase (LDH) activation of HCC cells. Transfection of siFBI-1 also decreased the expression of the Warburg-effect-related factors: hypoxia-inducible factor-1 alpha (HIF-1α), lactate dehydrogenase A (LDHA), or GLUT1, and the epithelial–mesenchymal transition-related factors, Vimentin or N-cadherin. The positive correlation between the expression of FBI-1 with HIF-1α, LDHA, or GLUT1 was confirmed in HCC tissues. Mechanistically, the miR-30c repressed the expression of HIF-1α by binding to the 3′-untranslated region (3′-UTR) of HIF-1α in a sequence-specific manner, and FBI-1 enhanced the expression of HIF-1α and HIF-1α pathway’s activation by repressing the expression of miR. By modulating the miR-30c/HIF-1α, FBI-1 promoted the Warburg effect or the epithelial–mesenchymal transition of HCC cells and promoted the resistance of HCC cells to molecular targeted agents.